Identifikasi Kebutuhan Penggunaan Teknologi Artificial Intelligence (AI) dalam Mendukung Pembelajaran Matematika yang Adaptif - Tyaningsih, Ratna Yulis; Gilang Primajati; Eka Kurniawan (Mandalika Mathematics and Educations Journal, 2024)
This study aims to identify the need for the use of Artificial Intelligence (AI) technology in supporting adaptive mathematics learning. The subjects of this research are students of the Faculty of Teacher Training and Education, University of Mataram, who are enrolled in mathematics courses. This is a descriptive study with a qualitative approach. The data collection instruments used are observation and questionnaires. The results of this study indicate that: (1) 96% of students are accustomed to using Artificial Intelligence (AI) technology for learning, with 31% reporting usage "every day" and 58,6% reporting usage "several times a week", etc.; (2) several AI-integrated applications commonly used by students include ChatGPT (Open AI), Gemini, Meta, Perplexity, Question AI, etc.; (3) AI technology is capable of providing students with more detailed information from various references, even by simply uploading a photo or image, and it can assist with academic tasks, though attention must still be given to limitations and ethics.